Effect of rotor induction and peak shaving on energy performance and cost of stationary unmoored floating offshore wind turbines - A. Babarit; M. André; V. Leroy (Wind Energy Science, 2025)
This paper investigates the effect of rotor induction and peak shaving on energy performance and cost of a stationary unmoored floating offshore wind turbine (SUFOWT). A SUFOWT is a floating offshore wind turbine (FOWT) for which a dynamic positioning (DP) system is used in lieu of a mooring system for station-keeping. It is particularly well suited for deployment in the far-offshore.